Studi Literatur: Penerapan Model Pembelajaran Probing-Prompting Terhadap Hasil Belajar Siswa - Eka Apriyanti; Ninah Wahyuni Amaliah; Emilia Ndia (Biology and Education Journal, 2022)
Literature Study: Application of The Probing-Prompting Learning Model to Student Learning Outcomes. The purpose of this study was to examine the application of the probing prompting learning model to student learning outcomes. The probing prompting learning model is learning that asks a series of questions that guide and test students' ideas to improve the thinking process that is able to connect students' knowledge and experience with newly learned knowledge. This research is a library research. The data collection technique was carried out by searching for scientific articles related to the research. The data obtained is secondary data in the form of books, magazines and scientific articles on research issues. The information obtained is processed through data reduction and then described scientifically to arrive at a research result. From the results of the study of several studies that have applied the probing prompting learning model, it can be concluded that the application of the probing prompting learning model has a positive effect on student learning outcomes.